Exergaming as a Viable Therapeutic Tool to Improve Static and Dynamic Balance among Older Adults and People with Idiopathic Parkinson’s Disease: A Systematic Review and Meta-Analysis - Harris, Dale M.; Rantalainen, Timo; Muthalib, Makii; Johnson, Liam; Teo, Wei-Peng (Frontiers in Aging Neuroscience, 2015)
The use of virtual reality games (known as ‘exergaming’) as a neurorehabilitation tool is gaining interest. Therefore, we aim to collate evidence for the effects of exergaming on the balance and postural control of older adults and people with idiopathic Parkinson’s disease (IPD). Six electronic databases were searched, from inception to April 2015, to identify relevant studies. Standardised mean differences (SMD) and 95% confidence intervals (CI) were used to calculate effect sizes between experimental and control groups. I2 statistics were used to determine levels of heterogeneity. 309 older adults and 74 people with IPD were assessed across eleven studies. The results showed that exergaming improved static balance (SMD 1.069, 95% CI 0.563 to 1.576), postural control (SMD 0.826, 95% CI 0.481 to 1.170) and dynamic balance (SMD -0.808, 95% CI -1.192 to -0.424) in healthy older adults. Two PD studies showed an improvement in static balance (SMD 0.124, 95% CI -0.581 to 0.828) and postural control (SMD 2.576, 95% CI 1.534 to 3.599). Our findings suggest that exergaming might be an appropriate therapeutic tool for improving balance and postural control in older adults, but more large-scale trials are needed to determine if the same is true for people with IPD.